Association between blood glucose levels and elective surgery delays in type II diabetes mellitus patients - Alfian Rajab; Rindani Toban; Lukman Sartika; Mulyati Mulyati; Irnawati Irnawati (Indonesian Nursing Journal, 2026)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia, which poses significant risks during the perioperative period. Elevated blood glucose levels are often associated with surgical complications, leading to the postponement of elective procedures. Purpose: This study aims to analyze the relationship between preoperative blood glucose levels and the delay of elective surgery in patients with Type II DM. Methods: A cross-sectional study was conducted among 100 patients with Type II Diabetes Mellitus undergoing elective surgery at Dr. La Palaloi Maros Hospital. The patients were selected using simple random sampling. Preoperative blood glucose levels were analyzed in relation to surgical readiness using the chi-square test. Results: The study found that 21% of patients experienced surgery delays, all delayed cases occurred among patients with preoperative blood glucose levels >200 mg/dL, while no delays were observed among patients with blood glucose levels below 200 mg/dL. Overall, 79.0% of patients proceeded with surgery as scheduled, whereas 21.0% experienced postponement due to uncontrolled hyperglycemia. Most respondents were aged 18–40 years (54%) and female (58%). A statistically significant relationship was found between blood glucose levels and elective surgery delays (p < .001). Conclusion: Preoperative blood glucose level is associated with elective surgery delays. Strict glycemic control before surgery is essential to reduce delays and improve perioperative patient safety.